2009
DOI: 10.1111/j.1440-1827.2009.02427.x
|View full text |Cite
|
Sign up to set email alerts
|

Sclerosing encapsulating peritonitis (abdominal cocoon) associated with liver cirrhosis and diffuse large B‐cell lymphoma: Autopsy case

Abstract: A case of sclerosing encapsulating peritonitis (SEP) associated with liver cirrhosis (LC) and complicated by diffuse large B-cell lymphoma (DLBCL) is reported herein. A49-year-old Japanese man had undergone peritoneovenous shunt against refractory ascites due to hepatitis C virus-positive uncompensated LC for 2 years. After he received a diagnosis of DLBCL of the left neck lymph node 3 months before his death, palliative care was given because of his poor general condition. He developed severe abdominal disten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Many hypotheses have been formulated to try to explain the primary aetiology, including viral peritonitis due to gynecological infection from retrograde menstruation. However, a number of cases have been reported in males and other age groups, which go against the support for these theories 1 3–5 7. Another theory is that the condition is an embryological abnormality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many hypotheses have been formulated to try to explain the primary aetiology, including viral peritonitis due to gynecological infection from retrograde menstruation. However, a number of cases have been reported in males and other age groups, which go against the support for these theories 1 3–5 7. Another theory is that the condition is an embryological abnormality.…”
Section: Discussionmentioning
confidence: 99%
“…Sclerosing encapsulating peritonitis is a rare complication whose incidence increases the longer the patient is receiving dialysis treatment. Other cases have been found to be associated with prior abdominal surgery, practolol (β-blocker) treatment, abdominal tuberculosis, sarcoidosis, cirrhosis and malignancy to name a few 1 6 7. There has also been a case report that describes a patient with a peritoneovenous shunt and diffuse large B-cell lymphoma that later developed sclerosing encapsulating peritonitis 7…”
Section: Discussionmentioning
confidence: 99%
“…SEP can be classified either as idiopathic or secondary to conditions such as peritoneal dialysis (PD), lupus, sarcoidosis, familiar Mediterranean fever, and use of beta blockers. 1 SEP has been reported in cirrhotic patients with [2][3][4] or without peritoneal-venous shunt (PVS). [5][6][7] It can also develop after liver transplantation (LT).…”
Section: Introductionmentioning
confidence: 99%
“…In the appropriate clinical setting, recognition of the entire dilated small bowel at the center of the abdomen and encased within a thick fibrocollageneous membrane, as though it were in a ‘cocoon,’ on a CT image is diagnostic of SEP. Yamada et al reported a case of SEP associated with liver cirrhosis and complicated by diffuse, large B cell lymphoma (1). There are reports of perforation of cocoon, particularly in immune-compromised patients which carries a high risk of mortality.…”
Section: Discussionmentioning
confidence: 99%